China’s water diplomacy in the Mekong : a paradigm shift and the role of Yunnan provincial government - Zhang, Hongzhou (2022)
This article examines the recent changes in China’s Mekong River policy and investigates the contributing factors. In the past few years, China has shifted from an upstream sovereignty stance to launch a multilateral transboundary water diplomacy initiative in the Mekong River basin through the Lancang-Mekong Cooperation Mechanism. We conclude that China’s adoption of water diplomacy in the Mekong River is partially attributable to international activism by the Yunnan provincial government and its associated actors.